Mesenchymal Stem Cell Aggregation‐Released Extracellular Vesicles Induce CD31+EMCN+ Vessels in Skin Regeneration and Improve Diabetic Wound Healing - Liu, Lu; Zheng, Chen‐Xi; Zhao, Na; Zhu, Ting; Hu, Cheng‐Biao; Zhang, Nan; Chen, Ji; Zhang, Kai‐Chao; Zhang, Sha; Liu, Jie‐Xi; Zhang, Kai; Jing, Huan; et al. (Advanced healthcare materials, 2023)
The blood vessel system is essential for skin homeostasis and regeneration. While the heterogeneity of vascular endothelial cells has been emergingly revealed, whether a regeneration‐relevant vessel subtype exists in skin remains unknown. Herein, a specialized vasculature in skin featured by simultaneous CD31 and EMCN expression contributing to the regeneration process is identified, the decline of which functionally underlies the impaired angiogenesis of diabetic nonhealing wounds. Moreover, enlightened by the developmental process that mesenchymal condensation induces angiogenesis, it is demonstrated that mesenchymal stem/stromal cell aggregates (CAs) provide an efficacious therapy to enhance regrowth of CD31+EMCN+ vessels in diabetic wounds, which is surprisingly suppressed by pharmacological inhibition of extracellular vesicle (EV) release. It is further shown that CAs promote secretion of angiogenic protein‐enriched EVs by proteomic analysis, which directly exert high efficacy in boosting CD31+EMCN+ vessels and treating nonhealing diabetic wounds. These results add to the current knowledge on skin vasculature and help establish feasible strategies to benefit wound healing under diabetic condition. Mesenchymal stem cell aggregates (MSC‐CAs) can provide an efficacious therapy to enhance regrowth of CD31+EMCN+ vessels in diabetic wounds, the decline of which functionally underlies the impaired angiogenesis of diabetic nonhealing wounds. Moreover, MSC‐CAs can secrete plenty of angiogenic protein‐enriched extracellular vesicles, which directly exert high efficacy in boosting CD31+EMCN+ vessels and treating nonhealing diabetic wounds.